If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying m + -6.5 = -10 Reorder the terms: -6.5 + m = -10 Solving -6.5 + m = -10 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '6.5' to each side of the equation. -6.5 + 6.5 + m = -10 + 6.5 Combine like terms: -6.5 + 6.5 = 0.0 0.0 + m = -10 + 6.5 m = -10 + 6.5 Combine like terms: -10 + 6.5 = -3.5 m = -3.5 Simplifying m = -3.5
| 8x^2+9x+7=0 | | 17x^7-3x^5+9x^4= | | 6+6x-1=11 | | 5x/x-2=7+10/x-2 | | 7x-5-(6-8X)+2=3x-17+68 | | 2(m+10)+7=39 | | 19x+2=18x+7 | | 4x^2-25x+88= | | f(12)=10(12) | | 7b^3=175b | | 7(y-1)=7y+2-5(-2y-1) | | 6(x)+4(x)=48 | | -5x^2-40x+y-88=0 | | -4(2n+5)=10n | | 13-1/8y=-9 | | 1-7/3x9 | | 11x=2x-99 | | 6t-11=-2t+5 | | 16x-4+2=-1 | | 5(j+3)=35 | | 4x-5=20x+7 | | x^2-14x-7=x^2-15x+2 | | -3p+10=1 | | -3+10=1 | | 3(7-7x)=105 | | -10+p+7=4 | | 7+2y-4=7y+21-3y | | 2(5T-7)=13T+8 | | 1+20x=19x+6 | | -10+p+7=-4 | | 14-3x=-8x+4 | | 14-3x=8x+4 |